Child Undernutrition in the States of India: An Analysis Based on Change in Composite Index of Anthropometric Failure from 2006 to 2016. Issue 1 (June 2021) - Jith, J. R.; Bedamatta, Rajshree
Stunting, wasting and underweight—the three traditional indicators of undernourishment among children—provide mutually non-exclusive categories of anthropometric failures: low height for age, low weight for height and low weight for age. Although these indicators are essential for designing specific clinical and child nutrition policy interventions, they fall short of estimating the prevalence of overall anthropometric failure, which provides a sense of the scale of the nutrition problem. This article estimates the alternative, more comprehensive measure Composite Index of Anthropometric Failure (CIAF) for Indian states, based on data from the National Family Health surveys of 2006 and 2016, for children under five years (Ch–U5). The CIAF-based undernutrition estimates show significantly high anthropometric failure levels among Indian children compared to only stunting, wasting and underweight. Based on population projections for Ch–U5, we also show that a sizeable number of states may have seen an increase in child undernutrition between 2006 and 2016. We also correlated CIAF with household wealth index scores and found a positive relationship with children facing no anthropometric failure.